Species Composition and Population Dynamics of Thrips (Thysanoptera) in Mango Orchards of Northern Peninsular Malaysia - H., Aliakbarpour; M. R., Che Salmah; Hamady, Dieng (Entomological Society of America, 2010)
Thrips are key pests of mango, Mangifera indica (L.), in Malaysia, including the Northern Peninsular. As Penang has year-round equatorial climate and high of rainfall, the populations of thrips may be subject to variations in composition and size. With a goal of developing an appropriate control strategy, a survey was conducted in Penang to determine species composition and abundance in relation to some environmental factors. Sprayed and unsprayed orchards were sampled on weekly basis through two ßowering seasons of 2009 using CO2 collection technique. Larval population falling into the ground to pupate and adults emerging from the soil were investigated in both orchards. Thrips hawaiiensis (Morgan) and Scirtothrips dorsalis (Hood) were the most prevalent species in the sprayed and the unsprayed orchards, respectively. The abundance of thrips was high during the ßowering period of the dry season and decreased during the ßowering period of the rainy season. This latter period coincided with decreased temperature and increased relative humidity. Percentage of adult emergence from the soil was lower in the rainy season than recorded in the dry season in both orchards. Taken together, these observations suggest that T. hawaiiensis and S. dorsalis are the main thrips species pests of mango panicles in Penang. Direct control with insecticides focusing on these two species may help to reduce cosmetic injuries and other damages on mango fruits.